MODERN METHODS OF ACNE TREATMENT IN CHILDREN - O. A. Nosachyova; R. M. Torshkhoeva; R. M. Torshkhoeva (Union of pediatricians of Russia, 2013)
The article is dedicated to one of the relevant issues of childhood and adolescence - acne. It describes modern approaches to acne treatment, including local, systemic and combined therapy and physiotherapeutic treatment methods. The article also presents foreign and Russian data on the use of different groups of drugs for acne therapy and peculiarities of acne treatment in pediatric practice.